Association between biomarkers for transfusion-transmitted infections and blood groups in donors from El Tocuyo, Lara, Venezuela (Revista Venezolana de Salud Pública, 2020)
Various studies in recent years links the ABO and Rh blood systems with different diseases such as ovarian or breast cancer, peptic ulcer, and even multiple sclerosis; however, when associated with transfusion-transmitted infections (TTI), controversy persists between their possible biological relationship. The early recognition of some biological or immunological phenotype prone to some TTIs, could be useful to help quickly identify patients at risk of suffering them. For this reason, the present research was aimed at determining the distribution of TTI and their specific association with ABO and Rh blood groups in blood donors who attended the Dr. Egidio Montesinos Hospital in the city El Tocuyo from Lara state, during the period 2010 to 2019. For this, 8362 blood samples were analyzed by the hemagglutination tube technique with monospecific sera to determine the ABO and Rh groups, as well as the seven TTI mandatory biomarkers performed in a venezuelan blood bank through the ELISA test of different biotech companies. It was found that the type O blood group was the most numerous as was the phenotype positive for the Rh blood system, a prevalence of 7 % was observed for any biological marker, with the indicator of hepatitis B being the most observed. The results show that TTI are commonly evidenced in the Rh-positive blood and with the blood group O. When researching the association between these uninominal variables with the Chi square test, it was found that there is a statistically significant association between the anti-HBc biomarker with both group O and the Rh-positive group, so it is concluded that the donors of the above-mentioned groups are likely to express hepatitis B.
Keywords: blood group antigens; biomarkers; transfusion-transmitted infections.